(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2002)
Thermal patterns of an area which underwent a polyphase deformation history such as the Carnic Alps were analyzed using the Colour Alteration Index (CAI) of conodonts in order to constrain some aspects of the metamorphic history of this part of the Southern Alps. Hercynian and alpine tectonothermal events were distinguished using CAI analysis. The Hercynian event developed temperatures up to low metamorphic conditions. Alpine tectonogenesis did not produce thermal levels in excess of the diagenetic zone. Moreover, CAI patterns allow recognition and evaluation of a hydrothermal metamorphic overprint of Permo-Triassic or Oligocene age that was superimposed on the pre-existing regional metamorphic zonation.